Reprogramming the EU's home affairs policy: Hostage to political short-termism? - Roderick Parkes; Daniela Kietz (Stiftung Wissenschaft und Politik (SWP), 2009)
The EU has begun work on the Stockholm Programme, a strategic document to guide its Justice and Home Affairs cooperation over the next five years. The upcoming negotiations offer a welcome chance to give some farsighted direction to the policy area. If the Commission's June proposal is anything to go by, however, efforts are focused upon immediate political pressures. Rather than entering a new bout of programming out of sheer habit and falling prey to short-termism, the EU needs to reflect about what this document can achieve for the medium-term
Keywords: 320